Critical Performance Roles of School Heads and Teachers' Collaboration in Public School - Malolos, Laila L. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
The study aimed to determine the critical performance roles among school heads and teachers’ collaboration in public schools. A quantita-tive descriptive correlation research design was used and the modified standardized survey instrument based on Total Leaders 2.0 by Spady (2010) was utilized in the 31 public schools with 538 teachers, school heads, and principals serving as the respondents. The test of the signif-icant difference between the assessment of the school heads and teach-ers as to critical performance roles among school heads indicates there is no significant relationship between groups and within groups by schools. There is a significant difference between the assessment of the school heads and teachers as to teachers’ collaboration. The perceived level of assessment of school heads and teachers as to teachers’ collabo-ration noted a significant. There is a significant relationship between the level of manifestation of critical leadership performance roles among school heads level of manifestation of teachers’ collaboration. Finally, the level of manifestation of critical leadership performance roles among school heads singly or in combination does not significant-ly explain the level of manifestation of teachers’ structural collabora-tion. The results show that critical performance roles positively pre-dicted Instructional Programs and Interpersonal Collaboration than in and of other variance.